Karakterisasi Morfologi Anggrek Epifit di Kawasan Wisata Curug Cibereum Selabintana Gunung Gede Pangrango Jawa Barat - Bela Prapitasari; Ardyan Pramudya Kurniawan (BIOSAINTROPIS (BIOSCIENCE-TROPIC), 2022)
The Curug Cibereum tourist area located in Selabintana, Sukabumi, is part of the Gunung Gede Pangrango National Park which consists of various types of orchids. This study aims to determine the types of epiphytic orchids in the Cibereum Curug Path based on the morphological characterization of epiphytic orchids, both stems, leaves, and flowers. The results of the study found as many as 31 species of epiphytic orchids from 11 genera. Based on the morphological observations of stems, pseudobulbs, leaves, and flowers on each type of epiphytic orchid, each has its characteristics. Observation of stem growth morphology found monopodial and sympodial orchids. The stems are found to belong short and do not even have stems but have pseudobulbs. The shape of the pseudobulb was found to be round, flattened, oval, and oval. Then for the shape of the leaves found lanceolate, oval, needle, and ovoid. As for the shape of flowers, each type has various shapes and colors. Some are big or small according to the species Keywords: Epiphytic Orchid, Cibereum Waterfall, Morphology, Characterization, Pseudobulb